Pengaruh Jarak Tempat Tinggal Dengan Kampus Terhadap Kosentrasi Belajar Mahasiswa Di Kelas - Floristia, Sella; Andhika, Sheila; Alawiyah, Tuti (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Concentration of learning is one of the vital things in lecturing activities, so distance is a challenge for every student to maintain concentration in learning. The purpose of this study was to determine the effect of distance between residence and campus on the concentration of learning in the classroom. The method used is to give a questionnaire to students of Biology Education 7C grade. The results of the study showed that in the first and second 5 minutes of learning, students were very concentrated and enthusiastic in learning. Whereas in the third and fourth minutes, students start to lack concentration in learning. The distance of a place to live near, more concentrated when learning takes place compared with the distance of a long house because more time and energy is spent making learning concentration reduced. To overcome this need a break before learning takes place and before learning to do ice breaking activities so that students do not get bored when the material will begin.